2017
DOI: 10.1097/dcc.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Management of Opioid and Sedative Weaning in Pediatric Congenital Heart Disease Patients

Abstract: Background: Opioid and sedative medications are commonly used to treat pediatric patients with congenital heart disease; however, their use is not without adverse effects. Symptoms of withdrawal can occur if the medications are discontinued abruptly or weaned too quickly. Objective: The aim of this study was to understand and describe the current management of opioid and sedative weaning in pediatric congenital heart disease patients in freestanding chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…36 A core activity of the C4-MNP is to establish the current state of specific pediatric cardiovascular nursing practices, identify variation, and develop recommendations to standardize practice across participating programs. 37 Established in 2011, the consortium includes nurses, advanced practice nurses, administrators, and scientists. 36,38…”
Section: Survey Populationmentioning
confidence: 99%
“…36 A core activity of the C4-MNP is to establish the current state of specific pediatric cardiovascular nursing practices, identify variation, and develop recommendations to standardize practice across participating programs. 37 Established in 2011, the consortium includes nurses, advanced practice nurses, administrators, and scientists. 36,38…”
Section: Survey Populationmentioning
confidence: 99%
“…In a recent survey of pediatric healthcare providers, only 27% of respondents utilized a written protocol for opioid tapering, 22% consulted a pain management team regarding weaning of opioids, and the majority seldom or never consulted a pharmacist [15]. In another survey of pediatric congenital heart disease centers, only 25% of sites used a standardized clinical pathway when weaning opioid medications [16]. In the RESTORE study—a randomized controlled multicenter study of protocolized sedation of 1225 pediatric patients—Curley et al demonstrated that the use of protocolized weaning of opioid medication was associated with shorter durations of opioid treatment (9 vs. 10 days, p = 0.01), and more study days spent in the calm and awake states (86% vs. 75%, p = 0.004) [14].…”
Section: Opioid-reduction Weaning Protocols In Pediatric Patientsmentioning
confidence: 99%
“…11 The C4-MNP has developed evidenced-based nurse-sensitive measures to use for assessment and improvement in nursing practice across the 31 collaborative paediatric cardiovascular programmes. [11][12][13] The Pediatric Cardiac Critical Care Consortium (PC 4 ; pc4quality.org) is a quality collaborative dedicated to improving care and outcomes for children and adults with critical congenital cardiovascular disease. 14 Started in 2009 with funding from the National Institutes of Health, PC 4 began with the launch of its clinical database.…”
Section: United States Quality Improvement Collaboratives In Cardiac mentioning
confidence: 99%